Effect of Limb Muscle Explosiveness and Balance Against Futsal Shooting Skills at Club The Brothers - Syaifullah, Syarif; Kahar, Irsan; Rahmatia, Rahmatia; Riswanto, A. Heri (Department of Physical Education, Sport, Health and Recreation, 2023)
The research objective was to determine the effect of leg muscle explosive power and balance on the ability to shoot futsal at Club The Brothers. The type of research used is descriptive research which is correlational in nature. The sample is part of a number of characteristics possessed by the population used for research. In this study, 10 members of The Brother FC were used as samples. The instruments used were the leg muscle explosive power test, balance test and shooting ability test. Data analysis techniques used in this study were descriptive tests, normality tests, linearity tests and regression tests using the SPSS Version 24.00 program. The results showed that the leg muscle explosive power variable had a tcount of 3.994 while ttable = 2.228 so tcount > ttable. The balance variable has tcount, which is 6.007, while ttable = 2.228, so tcount > ttable. From the results of data analysis, it was obtained that the Fcount was 65.878 and the sig. 0.000. Fcount value (65.878) > (2.228) and sig. smaller than 0.05 or a value of 0.000 <0.05. The conclusion is that the ability of the independent variables to explain variable variation is quite strong.